Persepsi Komunikasi Dalam Keluarga Dengan Anak Berkebutuhan Khusus: Studi Fenomenologi - Almadina Rakhmaniar (Institut Nalanda, 2023)
Research on communication in families with children with special needs explores the complexity of communication dynamics in such families, emphasizing the importance of understanding how parents and other family members interpret and adapt their communication styles to interact effectively with children. The study also explains the barriers faced by families in accessing rehabilitation services for children with special needs, highlighting systemic discrimination, socioeconomic factors, and health beliefs as major barriers